Determinants of Implanon discontinuation among women who use Implanon at Debre Berhan town public health institutions in Northeast Ethiopia: a case–control study - Chekole, Moges Sisay; Zikie, Delelegn Tsegaye; Wogie Fitie, Girma; Taye, Birhan Tsegaw; Kibiret, Desta Mekete; Silesh Zerihun, Mulualem; Moltot Kitaw, Tebabere; Ali, Mohamed Ahmed; Legasu, Temesegen Desalegn; Assefa, Kibir Temesgen; Lemma Demisse, Tesfanesh (Frontiers in Global Women's Health, 2023)
Background: Discontinuation of the most effective methods of contraception like Implanon is a worldwide problem, which is significantly associated with mistimed and unwanted pregnancies and unsafe abortion which has an increased risk of maternal and child mortality and morbidity. However, studies on factors associated with Implanon discontinuation in Ethiopia, particularly in this study area are limited. Therefore, this study aimed to identify the determinants of Implanon discontinuation among women who used Implanon at Debre Berhan town public health institutions. Methods and Materials: A facility-based unmatched case-control study was conducted among 312 study participants (78 cases and 234 controls) from February 1/ 2021 to April 30/2021. The study participants were selected by using a systematic random sampling method for controls, and cases were selected consecutively until the required sample size was reached, during the data collection period. The data were collected by using a structured face-to-face interviewer-administered questionnaire and entered into Epidata version 4.6 and transferred to SPSS version 25 for analysis. Variables with P-value <0.25 in the bivariable analysis were entered into the multivariable logistic regression model. In the final model variables with a p-value <0.05 were considered significant at a 95% confidence interval and the strength of association was measured using an Adjusted odds ratio. Results: In this study the determinants of Implanon discontinuation were; women who had no formal education [AOR: 3.57; 95% CI, (1.62, 7.87)] , having no children [AOR: 2.8 ; 95% CI, (1.50 , 5.17)], who had no counseling about side effect [AOR: 2.43;95% CI, (1.30 ,4.55), who had no discussion with their partner [AOR: 2.7 95% CI, (1.34 ,5.46)], who had no follow up appointment [AOR:2.81 ;95% CI), (1.54 ,5.12)], and who faced side effect [AOR :1.91 95% CI),(1.13 , 3.53)].Conclusion and Recommendations: Women's educational status, having no children during insertion of Implanon, no counseling about the side effect, no follow-up appointment, experienced side effect, and no discussion with a partner were determinants of Implanon discontinuation. Hence, healthcare providers and other health sector stakeholders should provide and strengthen pre-insertion counseling, and follow-up appointments to increase the retention of Implanon.